Rancang Bangun Trainer Sistem Pengisian dan Starter Serta Analisis Pengaruh Variasi Putaran Mesin terhadap Output Alternator dalam Efisiensi Pengisian Baterai - Achmad Rheza Zhuhudy; Muhammad Akhlis Rizza (Jurnal Kendali Teknik dan Sains, 2025)
The rapid development of automotive technology requires students majoring in automotive vocational schools (SMK), particularly in the field of vehicle charging and starting systems, to understand the charging and starting systems. Charging and starting systems are two crucial components in ensuring vehicle operation. For students, having a strong knowledge of how these systems work, maintain, and diagnose them is key to facing the challenges of the automotive industry. Therefore, improving the quality of automotive education is essential so that students can master the basic concepts and techniques needed to carry out their duties as automotive technicians. This research focuses on developing a trainer that can help vocational school students better understand and master vehicle charging and starting systems. The trainer, developed at SMK NU Sunan Ampel Tumpang, records real-world conditions in vehicles using components such as batteries, alternators, regulator ICs, starter motors, and other supporting electrical systems. One innovative feature added is testing the effect of variations in pulley ratios on alternator output voltage and current. This feature provides students with the opportunity to conduct hands-on experiments, analyzing how variations in pulley ratios can affect the performance of a vehicle's charging system. It is hoped that with this trainer, students will not only gain theoretical knowledge but also practical experience that will enable them to perform diagnoses, understand the working principles of charging and starting systems, and analyze system efficiency based on rotational speed measurements. Thus, students' competency in the automotive field can be improved, and they will be better prepared to face the increasingly complex world of work. The successful development of this trainer can also serve as a valuable reference for educators and the automotive industry in designing applicable and contextual learning strategies.